(untitled) (Fiep Bulletin - online, 2014)
The objective of this work was to analyze the relationship among waist circumference (WC), percentile of fat (%F), age and body mass index (BMI) in adults and children of both sexes. It is a study descriptive correlacional, where they were appraised 438 subjects, of these 284 they were adult and 154 children. The variables of corporal mass (kg), stature (cm), perimeter of the waist (cm), cutaneous folds were measured and later it was calculated BMI, WC and %F using Faulkner’s protocol (1968) for men, Jackson et al. (1980) for women and for children the protocols of Slaughter et al. (1988). To identify the relationship among the variables antropométrics the correlation of Pearson it was used, being adopted a level of significative of p <0,05. The results demonstrated that BMI presented a strong correlation with the %F, WC and age in the adults’ group. For the children’s group, the girls presented significant correlation among all the variables away as high as in adults, already in the boys there was significant correlation just between BMI and WC and %F and WC and% G. Like this, is ended that BMI and WC can be used in the diagnosis of excess of corporal fat, because they presented a good correlation with the% G and another measured antropométrics.